Tendon optimization for prestressed concrete structures using genetic algorithms - Houšť, Vladimír; Mašek, Jan; Eliáš, Jan (ACHE, 2025)
The contribution presents a computer code that optimizes a prestress tendon force and geometry. The mechanical part computes time-dependent analysis of the prestress concrete structure taking into account shrinkage, creep, tendon relaxation, friction and anchor slip, i.e., all necessary components of prestress short- and long-term losses. The optimization part executes genetic algorithm with chosen parameters of the tendon geometry subjected to optimization with respect to mechanical and geometrical constraints. The minimized variable is prestressing force. A parametric study of a 3-span post-tensioned bridge deck is presented in the last section.

The contribution presents a computer code that optimizes a prestress tendon force and geometry. The mechanical part computes time-dependent analysis of the prestress concrete structure taking into account shrinkage, creep, tendon relaxation, friction and anchor slip, i.e., all necessary components of prestress short- and long-term losses. The optimization part executes genetic algorithm with chosen parameters of the tendon geometry subjected to optimization with respect to mechanical and geometrical constraints. The minimized variable is prestressing force. A parametric study of a 3-span post-tensioned bridge deck is presented in the last section.
Tendon optimization for prestressed concrete structures using genetic algorithms
Keywords: prestressed concrete; tendon optimization; time-dependent analysis; Genetic algorithm; prestressed concrete; tendon optimization; time-dependent analysis; Genetic algorithm